The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2008
DOI: 10.1111/j.1745-3933.2008.00453.x
|View full text |Cite
|
Sign up to set email alerts
|

A downward revision to the distance of the 1806−20 cluster and associated magnetar from Gemini Near-Infrared Spectroscopy

Abstract: We present H‐ and K‐band spectroscopy of OB and Wolf–Rayet (WR) members of the Milky Way cluster 1806−20 (G10.0–0.3) to obtain a revised cluster distance, of relevance to the 2004 giant flare from the (soft gamma repeater) SGR 1806−20 magnetar. From GNIRS (Gemini Near‐Infrared Spectrograph) spectroscopy obtained with Gemini South, four candidate OB stars are confirmed as late O/early B supergiants, while we support previous mid‐WN and late WC classifications for two WR stars. Based upon an absolute Ks‐band mag… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
120
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 114 publications
(127 citation statements)
references
References 28 publications
7
120
0
Order By: Relevance
“…Different physical mechanisms can generate similar H−K s and J − H colors; LBVs have J−K s colors from ∼1.0 to ∼5.0 mag, and H−K s from ∼0.2 mag to ∼2.0 mag. A sample of five LBVs (AFGL2298, Pistol Star, WR102ka, LBV1806−20, G0.120−0.048, FMM362) have redder J−K s , which are consistent with distant sources at large interstellar extinction (A K s = 3.15, 2.99, 2.78, 3.0, 3.26, 3.42 mag, respectively Clark et al 2003;Mauerhan et al 2010;Barniske et al 2008;Bibby et al 2008).…”
Section: H-k S Versus J-h Diagrammentioning
confidence: 79%
“…Different physical mechanisms can generate similar H−K s and J − H colors; LBVs have J−K s colors from ∼1.0 to ∼5.0 mag, and H−K s from ∼0.2 mag to ∼2.0 mag. A sample of five LBVs (AFGL2298, Pistol Star, WR102ka, LBV1806−20, G0.120−0.048, FMM362) have redder J−K s , which are consistent with distant sources at large interstellar extinction (A K s = 3.15, 2.99, 2.78, 3.0, 3.26, 3.42 mag, respectively Clark et al 2003;Mauerhan et al 2010;Barniske et al 2008;Bibby et al 2008).…”
Section: H-k S Versus J-h Diagrammentioning
confidence: 79%
“…(1) Bibby et al 2008; (2) Kouveliotou et al 1998; (3) Kouveliotou et al 1999. shown that the effects of mass transfer onto a companion star significantly reduce the RSG lifetime (Eldridge et al 2008). This enables the core to retain angular momentum through to SN, enough perhaps to greatly amplify the resulting neutron star's magnetic field through the dynamo mechanism in the first few seconds of its life.…”
Section: The Possible Role Of Binaritymentioning
confidence: 99%
“…This leads to L PL X = 4.1×10 35 erg s −1 . If we use instead the revised distance of 8.7 kpc (Bibby et al 2008), we have L PL X = 1.4 × 10 35 erg s −1 . Figure 7 shows the ratio L PL X /Ė rot as a function of the NS mass in the case of SGR 1900+14 and SGR 1806-20, adopting the GM1 EOS and assuming a distance of 15 kpc for both sources.…”
Section: Sgrs and Axps Efficiencymentioning
confidence: 99%